Exploring the link between Atmospheric conditions and Acid rain prevalence: a 12-year study at Juanda International Airport, Sidoarjo, Indonesia. - Mayasari, Agatha; Yulfiah, Yulfiah (Journal of Earth and Marine Technology (JEMT), 2023)
Acid rain is a pressing environmental concern, posing severe threats to the well-being of various forms of life. Our research sought to evaluate the acidity level of rainwater at Juanda International Airport, attempting to correlate it with weather parameters. We analyzed a span of twelve years, inspecting the relationship of rainwater pH with upper atmospheric conditions, specifically focusing on air temperature and humidity. Utilizing a statistical approach enabled us to draw meaningful conclusions from the extensive data at hand. Our analysis revealed that a significant 40% of the rain data fell under the acid rain category, demonstrating the alarming prevalence of the phenomenon in the region. A fascinating insight uncovered through our study was the existence of a correlation between the pH level of the rainwater and the air temperature and humidity values, particularly in zones where rain clouds tend to develop. This finding amplifies our understanding of the intricate relationships between acid rain formation and atmospheric conditions. We posit that weather parameters like temperature and humidity may have an integral role in acid rain production, thereby influencing the ecosystem's balance. Continued research in this realm can potentially help in creating better predictive models and in devising effective strategies for combating the devastating effects of acid rain.